2020
DOI: 10.2337/db19-1094
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T Parallels Structural Nerve Damage in Type 2 Diabetes: A Cross-sectional Study Using Magnetic Resonance Neurography

Abstract: COMPLICATIONS that different patterns of nerve damage can be attributed to different risk factors (e.g., hyperglycemia and dyslipidemia), and that diffusion tensor imaging (DTI) allows for a very accurate assessment of the structural integrity of affected nerves (13-15). This study combined hsTNT and proBNP assays with results derived from automated nerve fiber segmentation after 3T DTI MRN, as well as clinical, electrophysiological, and serological testing, to investigate whether hsTNT and proBNP may serve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
5
42
0
Order By: Relevance
“…One must consider, however, that all images used in this study were acquired at the same scanner and that DRG signal intensity was normalized to adjacent muscle tissue, which should make the results reproducible. In future studies, quantitative T2 imaging of DRG and the assessment of other quantitative MRN imaging parameters such as proton density and fractional anisotropy, that have been shown to be accurate markers of structural peripheral nerve integrity for different neuropathies, should be investigated ( Godel et al, 2016 ; Kollmer et al, 2018 ; Jende et al, 2019b , 2020 ; Sollmann et al, 2019 ; Sato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One must consider, however, that all images used in this study were acquired at the same scanner and that DRG signal intensity was normalized to adjacent muscle tissue, which should make the results reproducible. In future studies, quantitative T2 imaging of DRG and the assessment of other quantitative MRN imaging parameters such as proton density and fractional anisotropy, that have been shown to be accurate markers of structural peripheral nerve integrity for different neuropathies, should be investigated ( Godel et al, 2016 ; Kollmer et al, 2018 ; Jende et al, 2019b , 2020 ; Sollmann et al, 2019 ; Sato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DN is generally acknowledged to be a late complication of diabetes that starts at the level of the feet and then progresses further upwards until, at later stages, the upper limbs become involved as well, starting at the level of the hands (Nawroth et al, 2018). In contrast to the progression of clinical symptoms, recent studies applying high-resolution magnetic resonance neurography (MRN) at three Tesla (3T) have come to show that nerve lesions predominate proximally at the level of the sciatic nerve and that the sciatic nerve's fractional anisotropy (FA), a dimensionless quantity for directed diffusion in nerve tissue, is a highly sensitive parameter for structural nerve damage in patients with diabetic neuropathy in previous clinical studies (Vaeggemose et al, 2017b;Jende et al, 2019Jende et al, , 2020a. Despite the assumption that length-dependent nerve damage in DN starts at the level of the feet and progresses to further proximally with an involvement of the upper limbs at later stages, recent studies revealed that sensory and motor functions of the upper limb are frequently affected already at early stages of DN but often remain undiagnosed until a certain degree of functional impairment becomes apparent, indicating that the progression of nerve fiber damage at the level of the hands and arms may parallel the progression of nerve fiber damage at the level of the feet and legs (Kopf et al, 2018a;Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a frequent metabolic disorder with several complications that are typically associated with macroand microangiopathic alterations (Madonna et al, 2017;Jende et al, 2019a). Increased markers of microangiopathy have been implicated in peripheral neuropathy and cardiac myopathy, and linked to mitochondrial dysfunction (Amano, 2016;Jia et al, 2018;Smyrnias et al, 2019;Jende et al, 2020). Although an impressive body of knowledge exists about the role played by mitochondrial dysfunction in diabetes, the mechanisms underlying their impact on diabetic cardiomyopathy, a severe and potentially lethal complication that limits T1DM patients' life expectancy and quality of life, are still not well understood (Aon and Foster, 2015).…”
Section: Introductionmentioning
confidence: 99%